Potential for Lead Release from Lead-Immobilized Animal Manure Compost in Rhizosphere Soil of Shooting Range - Masahiko Katoh; Wei Lu; Takeshi Sato (Applied and Environmental Soil Science)
This study aimed to clarify the magnitude of lead release from lead-sorbed animal manure compost (AMC) in rhizosphere soil compared with nonplanted soil of shooting range. The presence of buckwheat caused reduction in rhizosphere soil pH and enhancement in the level of water-soluble organic carbon compared with those of nonplanted soil. In addition, the presence of buckwheat altered the lead phases and increased the relative amount of the soluble exchangeable fraction, resulting in increase in the CaCl2-soluble lead level. In contrast, the presence of Guinea grass did not change the lead bioavailability or phases compared with nonplanted soil. Lead release tests in solution showed that between solution pH 5 and solution pH 7 the amount of lead released from the compost was higher in the rhizosphere soil of buckwheat than in nonplanted soil, whereas there was no significant difference between the rhizosphere soil of Guinea grass and nonplanted soil. These results suggest that the increase in the quantity of exchangeable lead resulting from the rhizosphere effect induces lead immobilized by the AMC to be remobilized. Therefore, AMC should be applied to soils that contain plants that are unable to alter the lead phases in the shooting range soil. Efforts should be particularly made to ensure that lead cannot be transformed to the exchangeable phase.